A multisport epidemiologic comparison of anterior cruciate ligament injuries in high school athletics - Joseph, A. M.; Collins, C. L.; Henke, N. M.; Yard, E. E.; Fields, S. K.; Comstock, R. D. (Journal of Athletic Training, 2013)
Background: The knee joint is the second most commonly injured body site after the ankle and the leading cause of sport-related surgeries. Knee injuries, especially of the anterior cruciate ligament (ACL), are among the most economically costly sport injuries, frequently requiring expensive surgery and rehabilitation. Objective: To investigate the epidemiology of ACL injuries among high school athletes by sport and sex. Design: Descriptive epidemiology study. Main Outcome Measure(s): Using an Internet-based data-collection tool, Reporting Information Online (RIO), certified athletic trainers from 100 nationally representative US high schools reported athlete-exposure and injury data for athletes from 9 sports during the 2007/08-2011/12 academic years. The outcome of interest in this study was ACL injuries. Results: During the study period, 617 ACL injuries were reported during 9?452?180 athlete exposures (AEs), for an injury rate of 6.5 per 100.000 AEs. Nationally, in the 9 sports studied, an estimated 215?628 ACL injuries occurred during the study period. The injury rate was higher in competition (17.6) than practice (2.4; rate ratio [RR] = 7.3, 95% confidence interval [CI] = 6.08, 8.68). Girls' soccer had the highest injury rate (12.2) followed by boys' football (11.1), with boys' basketball (2.3) and boys' baseball (0.7) having the lowest rates. In sex-comparable sports, girls had a higher rate (8.9) than boys (2.6; RR = 3.4, 95% CI = 2.64, 4.47). Overall, 76.6% of ACL injuries resulted in surgery. The most common mechanisms of injury were player-to-player contact (42.8%) and no contact (37.9%). Conclusions: Anterior cruciate ligament injury rates vary by sport, sex, and type of exposure. Recognizing such differences is important when evaluating the effectiveness of evidence-based, targeted prevention efforts.